Synthesis, Characterization and Cytotoxicity Evaluation of New Biimidazole Palladium(II) Complexes with Thioureas - Spinardi Franchi, Silmar Jose; Souza, Rodrigo Alves de [UNESP]; Mauro, Antonio Eduardo [UNESP]; Carlos, Iracilda Zeppone [UNESP]; Abreu Ribeiro, Livia Carolina de [UNESP]; Rocha, Fillipe Vieira; Godoy-Netto, Adelino Viera de [UNESP] (Slovensko Kemijsko Drustvo, 2018)
The reactions between [PdCl2(tmbiimH(2))]center dot H2O (1) {tmbiimH(2) = 2,2'-bis(4,5-dimethylimidazole)} and thiourea (tu), N-methylthiourea (mtu), N-phenylthiourea (ptu), N,N'-dimethylthiourea (dmtu) or N,N'-diphenylthiourea (dptu) in the 1:2 molar ratio resulted in the compounds [PdL2(tmbiimH(2))]Cl-2 center dot nH(2)O{L = tu (2), mtu (3), ptu (4), dmtu (5) and dptu (6)}, which were characterized by elemental analyses, infrared (IR), and H-1 NMR spectroscopies and conductivity measurements. The IR spectra of 1-6 were consistent with the presence of chelating tmbimH(2) ligand. All compounds and cisplatin were tested in vitro by MTT assay for their cytotoxicity against three murine cancer cell lines: mammary adenocarcinoma (LM3), lung adenocarcinoma (LP07) and mouse fibroblast (L929) cells. Relating the series of compounds to their biological activities we found compound 6 as the most promising of them.
Keywords: 2,2 '-bis(4,5-dimethylimidazole); Thioureas; Cytotoxicity; Cancer